Disrupting PTPRJ transmembrane-mediated oligomerization counteracts oncogenic receptor tyrosine kinase FLT3 ITD - Schwarz, Marie; Rizzo, Sophie; Paz, Walter Espinoza; Kresinsky, Anne; Thévenin, Damien; Müller, Jörg P. (Frontiers in Oncology, 2022)
The receptor protein tyrosine phosphatase (RPTP) PTPRJ (also known as DEP-1) has been identified as a negative regulator of the receptor tyrosine kinase FLT3 signalling in vitro. The inactivation of the PTPRJ gene in mice expressing the constitutively active, oncogenic receptor tyrosine kinase FLT3 ITD aggravated known features of leukaemogenesis, revealing PTPRJ’s antagonistic role. FLT3 ITD mutations resulting in constitutively kinase activity and cell transformation frequently occur in patients with acute myeloid leukaemia (AML). Thus, in situ activation of PTPRJ could be used to abrogate oncogenic FLT3 signalling. The activity of PTPRJ is suppressed by homodimerization, which is mediated by transmembrane domain (TMD) interactions. Specific Glycine-to-Leucine mutations in the TMD disrupt oligomerization and inhibit the Epidermal Growth Factor Receptor (EGFR) and EGFR-driven cancer cell phenotypes. To study the effects of PTPRJ TMD mutant proteins on FLT3 ITD activity in cell lines, endogenous PTPRJ was inactivated and replaced by stable expression of PTPRJ TMD mutants. Autophosphorylation of wild-type and ITD-mutated FLT3 was diminished in AML cell lines expressing the PTPRJ TMD mutants compared to wild-type-expressing cells. This was accompanied by reduced FLT3-mediated global protein tyrosine phosphorylation and downstream signalling. Further, PTPRJ TMD mutant proteins impaired the proliferation and in vitro transformation of leukemic cells. Although PTPRJ’s TMD mutant proteins showed impaired self-association, the specific phosphatase activity of immunoprecipitated proteins remained unchanged. In conclusion, this study demonstrates that the destabilization of PTPRJ TMD–mediated self-association increases the activity of PTPRJ in situ and impairs FLT3 activity and FLT3-driven cell phenotypes of AML cells. Thus, disrupting the oligomerization of PTPRJ in situ could prove a valuable therapeutic strategy to restrict oncogenic FLT3 activity in leukemic cells.